Estudo sobre o comportamento estrutural de pavimentos de edifícios com lajes sem vigas com a presença de furos e aberturas - Oliveira, Luis Gustavo Simão de (2018)
This research presents a structural analysis of flat plates in reinforced concrete with the introduction of openings in regions established by foreign standards (ACI318: 14), whereas NBR 6118 (ABNT, 2014) doesn’t make any recommendations about dimensions and positioning of possible openings that may exist in the structural system. Firstly, a comparative analysis of the results was done using the analitic calculation methods (Direct Method and Equivalent Gate Method) and the Finite Element Method using the SAP2000® v.16 software on flat plates. In a second moment, the openings were introduced in accordance with ACI 318: 14 as the initial parameter for such design and used only SAP2000® v.16 software for analysis. The reactions of bending moments and transversal displacements caused by these efforts were compared, as well as presenting the required amount of steel and its distribution throughout the structure. 57 slabs were modeled with the purpose of verifying the coherence of the manual calculation methods and analyzing the influence of the openings on the flat plates system, presenting as variables the slab thickness, dimensions of the openings and their positioning. As a result, the study provides satisfactory conclusions regarding the maximum openings slab stipulated by ACI 318: 14 when comparing its efforts and displacement reactions with slabs without openings, beyond to be able to verify the behavior of the structure when inserting openings that exceed these limits. For the analysis of slabs without openings, it was possible identify distinct characteristics that each calculation method provided from its results.